KERAGAMAN SUBSTRAT BAGI NUDIBRANCH DI SELAT LEMBEH - Yehezkiel S.P.H. Marpaung; Medy Ompi; Indri Manembu; Kakaskasen A. Roeroe; N. Gustaf F. Mamangkey; Lucky Lumingas (JURNAL PESISIR DAN LAUT TROPIS, 2019)
Research on the diversity of nudibranch substrates was carried out in Lembeh Strait at 3 locations, at Nudifall, Makawide, and Nudiritrit.  The purpose of the researchs 1) to discover the nudibranch species at Nudifall, Makawide, Nudiritrit in the Lembeh Strait. 2) to knowing the substrate occupied by nudibranchs in the Lembeh Strait. 3) to knowing the overlapping substrate that was occupied by the nudibranch. Subtrates can to be used by nudibranches to get food sources, shelter from predators, and as a place to live. Nudibranch species found in the Lembeh Strait were 19 species in this study. Dead Coral with Algae (DCA), sponges, algae, hard coral, and tunicates were the types of substrate where nudibranches live in the Lembeh Strait The most dominant or overlapping substrate between types of nudibranchs was Dead Coral with Algae. Keywords : Nudibranch, Substrate, Lembeh Substrate diversity of nudibranch at Lembeh Strait            Penelitian mengenai keragaman substrat nudibranch dilakukan di Selat Lembeh pada 3 lokasi yaitu Nudifall, Makawide, dan Nudiritrit.  Tujuannya yaitu 1) mengetahui jen nudibranch di Nudifall, Makawide, Nudiritrit di Selat Lembeh. 2) mengetahui substrat yang ditempati nudibranch di Selat Lembeh. 3) mengetahui substrat yang tumpang tindih (overlap) yang ditempati oleh nudibranch. Subtrat dapat dimanfaatkan oleh nudibranch untuk mendapatkan sumber makanan, tempat berlindung dari predator, dan sebagai tempat tinggal.  Jenis nudibranch yang ditemukan di Selat Lembeh ada 19 spesies dalam penelitian ini.  Dead Coral with Algae (DCA), spons, alga, hard coral, dan tunikata merupakan substrat-substrat tempat hidup nudibranch di Selat Lembeh. Substrat yang paling dominan atau tumpang tindih antar jenis dari nudibranch adalah DCA. Kata kunci : Nudibranch, Substrat, Lembeh.